Hepatomegaly as the first symptom of malignant solid tumors in children - Widłak, Karolina; Prządka, Marta; Chromiec, Tomasz; Kulczyński, Marcin; Nurzyńska-Flak, Joanna (Journal of Education, Health and Sport, 2018)
Introduction: Hepatomegaly is a physical symptom that may suggest primary liver disease, or it may be present as a component of the generalized disorder. One of uncommon reasons of hepatomegaly, which occur in children of all ages, but most common in infants and toodlers, are primary and metastatic neoplasms, such as hepatoblastoma (HB) and neuroblastoma (NB).The aim of this work is to prove how significant implementation of appropriate diagnostics after detecting hepatomegaly in a child is by presenting an example of two patients’ medical history.Cases report: A 3-month-old girl and a 2-year-old boy were admitted to the Department of Pediatric Hematooncology because of the tumors, which were detected in abdominal ultasound examinations. The examinations were performed in order to find the causes of growing abdominal circumferences observed by the parents and significant hepatomegaly, which were shown in physical examination of both children. A tumor of the right adrenal gland with numerous metastatic changes in the liver was detected in the girl and a single tumor coming out most likely from the liver was revealed in the boy. Laboratory tests have shown a significant increase in the levels of tumor markers: NSE in the girl (51 μg/l) and AFP (327 830 U/ml) in the boy. On the basis of the performed tests’ results, the girl was suspected to have NB with liver metastases and the boy appeared to have HB with lung metastases, inferior vena cava and right hepatic vein invasion.Conclusions: Attention should be paid to palpation and percussion examination of the abdomen in order to detect hepatomegaly at the earliest possible stage. It is important to implement appropriate diagnostics after detecting the enlargement of the liver in a child, because this symptom may be a sign of developing dangerous tumor process.